Synergistical Enhancement of Thermoelectric Properties in n‐Type Bi2O2Se by Carrier Engineering and Hierarchical Microstructure. Issue 31 (8th July 2019) - Tan, Xing; Liu, Yaochun; Liu, Rui; Zhou, Zhifang; Liu, Chan; Lan, Jin‐Le; Zhang, Qinghua; Lin, Yuan‐Hua; Nan, Ce‐Wen
Abstract: Oxygen‐containing compounds are promising thermoelectric (TE) materials for their chemical and thermal stability. As compared with the high‐performance p‐type counterparts (e.g., ZT ≈1.5 for BiCuSeO), the enhancement of the TE performance of n‐type oxygen‐containing materials remains challenging due to their mediocre electrical conductivity and high thermal conductivity. Here, n‐type layered Bi2 O2 Se is reported as a potential TE material, of which the thermal conductivity and electrical transport properties can be effectively tuned via carrier engineering and hierarchical microstructure. By selective modification of insulating [Bi2 O2 ] 2+ layers with Ta dopant, carrier concentration can be increased by four orders of magnitude (from 10 15 to 10 19 cm −3 ) while relatively high carrier mobility can be maintained, thus greatly enhancing the power factors (≈451.5 µW K −2 m −1 ). Meanwhile, the hierarchical microstructure can be induced by Ta doping, and the phonon scattering can be strengthened by atomic point defects, nanodots of 5–10 nm and grains of sub‐micrometer level, which progressively suppresses the lattice thermal conductivity. Accordingly, the ZT value of Bi1.90 Ta0.10 O2 Se reaches 0.36 at 773 K, a ≈350% improvement in comparison with that of the pristine Bi2 O2 Se. The average ZT value of 0.30 from 500 to 823 K is outstanding among n‐type oxygen‐containing TE materials. This work provides a desirable way for enhancing the ZT values in oxygen‐containing compounds. Abstract : By selective modification of insulating [Bi2 O2 ] 2+ layers of n‐type Bi2 O2 Se with a Ta dopant, carrier concentration can be increased by four orders of magnitude. The phonon scattering can be strengthened in the hierarchical microstructure. The average ZT value of 0.30 from 500 to 823 K is outstanding among n‐type oxygen‐containing thermoelectric materials.